MODEL KELEMBAGAAN PEMBERDAYAAN EKONOMI MASYARAKAT DESA MELALUI WAKAF - Mohamad Ainun Najib; Najmudin Najmudin; Isti Nuzulul Atiah (Asy-Syari'ah, 2021)
Abstract: Economic justice in the State of Indonesia is still far from what is aspired, plus large foreign credits, causing various problems, especially poverty. Islamic economists provide a solution with waqf to answer these problems. This study aims to determine the pattern of waqf management, the waqf empowerment system for the village community's economy, as well as the waqf institutional model which is used as an instrument of economic empowerment for rural communities in Pontang sub-district, Serang district. This study uses a normative juridical scientific approach, among these approaches are the approaches taken, including: the statute approach, the concept approach, and the sociological approach. The data collected consists of primary and secondary data. The Miles and Hubermen model method was used as a data analysis method. The results of this study indicate that the pattern of waqf management in the villages of the Pontang sub-district is managed by the nazdir of the organization, namely the Mosque and Foundation Prosperity Council. Waqf-based community economic empowerment system for youth groups and farmers. The waqf institutional model is simple and carried out independently, there is no coordination between waqf managers and Badan Wakaf Indonesia (BWI) as the parent organization of waqf management. The results of this study contribute to knowledge about the concept of waqf management in rural areas, patterns of empowerment with effective waqf and in rural areas, as well as input for BWI in improving waqf governance.Abstrak: Keadilan ekonomi  di  Negara  Indonesia  masih  jauh  dari  yang   dicita-citakan, ditambah pinjaman luar negeri yang besar, menyebabkan  permasalahan kemiskinan. Para  ekonom Islam memberikan solusi dengan wakaf untuk menjawab permasalahan tersebut. Penelitian ini bertujuan untuk mengetahui pola manajemen wakaf, sistem pemberdayaan wakaf terhadap ekonomi masyarakat desa, serta model kelembagaan wakaf yang dijadikan instrumen pemberdayaan ekonomi masyarakat desa Kecamatan Pontang Kabupaten Serang. Penelitian ini menggunakan pendekatan saintifik yuridis normatif, yaitu di antaranya adalah pendekatan perundang-undangan (statute approach), pendekatan konsep, dan pendekatan sosiologis atau empiris. Data yang dikumpulkan terdiri dari data primer dan sekunder. Metode model Miles dan Huber-men digunakan sebagai metode analisis data. Hasil penelitian ini menunjukkan bahwa pola manajemen wakaf di desa-desa Kecamatan Pontang  dikelola oleh nazdir organisasi yaitu Dewan Kemakmuran Masjid dan Yayasan. Sistem pemberdayaan ekonomi masyarakat  berbasis  wakaf  menyentuh  kelompok pemuda dan petani. Model kelembagaan wakaf bersifat sederhana dan dilakukan secara mandiri, belum ada koordinasi antara pengelola wakaf dengan Badan Wakaf Indonesia (BWI) sebagai organisasi induk pengelolaan wakaf. Hasil penelitian ini memberikan kontribusi pengetahuan tentang konsep manajemen wakaf di pedesaan, pola pemberdayaan dengan wakaf yang efektif dan efisien di pedesaan, sekaligus masukan bagi BWI dalam peningkatan tata kelola wakaf.